City-to-city exchange: redefining "resilience" in the Arab region. Issue 4 (29th August 2019) - Eltinay, Nuha
Abstract : Purpose: It might seem plausible to argue that effective monitoring of disaster data loss can help achieve progress in reporting to the Sendai Framework for Disaster Risk Reduction (SFDRR) and the global targets of sustainable development goals and associated indicators. Nevertheless, with the lack of climate change and disaster data losses in the Arab region, the integration of risks associated with socio-economic dimensions at the wider scale of displacement is important to shape a regional understanding of resilience terminology and provides the means of translating it. The purpose of this paper is to identify the means of redefining "Resilience" in the Arab region context of climate change, conflict and displacement in association with the theoretical principles of the "fragile city". Design/methodology/approach: In an attempt to achieve the SFDRR target (E) "substantially increase the number of countries with national and local DRR strategies by 2020, " this study investigates the use of the (United Nations Office for Disaster Risk Reduction) disaster resilience scorecard as a guiding principle for city-to-city (C2C) resilience-building knowledge exchange between Amman (Jordan) and Khartoum (Sudan). Findings: Facing similar urban challenges against disaster and violent conflict-protracted displacement, the study findings indicate that the C2C exchange program was useful in understanding the cities' urban risk profiles, promoting dialogue among local governments and creating a culture of learning organizations for knowledge sharing on DRR governance and beyond. However, the applied resilience assessments overlooked the qualitative and socio-ecological understanding of climate change risk and human security principles among the most vulnerable groups of refugees and internally displaced persons in fragile settings. This is recommended to be integrated into building coherence for resilience across the 2015-2030 Global Agendas reporting and monitoring mechanisms, leaving "no one behind". Originality/value: The C2C exchange program for Amman and Khartoum was an opportunity for understanding the cities' urban risk profiles, addressing challenges and building "decentralized cooperation" beyond the cities' institutional boundaries (UN Habitat, 2001 ), with recommendations for "selecting resilience indicators specific to fragile cities" to quantitatively measure disaster displaced persons' (DDPs) vulnerabilities and current status of "income and social equality, microeconomic security, provision of basic services and social protection" while providing qualitative evidence on "social cohesion, social networks/social support and local government–community cooperation" (Patel and Nosal, 2016 ).